2011
DOI: 10.1016/j.matbio.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Type XVII collagen (BP180) can function as a cell−matrix adhesion molecule via binding to laminin 332

Abstract: Collagen XVII (COL17) is a transmembrane glycoprotein that is expressed on the basal surface of basal epidermal keratinocytes. Previous observations have led to the hypothesis that an interaction between COL17 and laminin 332, an extracellular matrix protein, contributes to the attachment of the basal keratinocyte to the basement membrane. In order to isolate and manipulate COL17 interactions with ECM components, we induced COL17 expression in two cells lines, SK-MEL1 and K562, that exhibit little or no capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…In vivo subepidermal blistering is observed when expression of BP180 is reduced or absent because of gene knockout in mice or mutation in humans with generalized atrophic benign epidermolysis bullosa (6,49). Van den Bergh and colleagues (50) demonstrated that in cells that lack other hemidesmosomal components, cell matrix attachment is directly related to the amount of BP180 expression. In this study, we demonstrate that BP autoantibodies decrease confluence of cultured keratinocytes and the number of hemidesmosomes localized at the BMZ of organ cultured skin.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo subepidermal blistering is observed when expression of BP180 is reduced or absent because of gene knockout in mice or mutation in humans with generalized atrophic benign epidermolysis bullosa (6,49). Van den Bergh and colleagues (50) demonstrated that in cells that lack other hemidesmosomal components, cell matrix attachment is directly related to the amount of BP180 expression. In this study, we demonstrate that BP autoantibodies decrease confluence of cultured keratinocytes and the number of hemidesmosomes localized at the BMZ of organ cultured skin.…”
Section: Discussionmentioning
confidence: 99%
“…The protein contributes to keratinocyte adhesion by interacting with extracellular matrix proteins such as laminin 332 (Fig. 3b) (105,106).…”
Section: Bullous Pemphigoid and Its Target Autoantigensmentioning
confidence: 99%
“…It is notable that some interactions between cell-associated receptors and collagens occur indirectly as, for instance, in the case of the platelet receptor GP I that interacts with collagens by the intermediate of von Willebrand Factor (vWF) (Leitinger & Hohenester, 2007). Finally, it is important to mention that some collagens (XIII, XVII, XXIII and XXV) act themselves as membrane receptors to components of the BM like Ln or collagen IV (Qiao et al, 2009;Van den Bergh et al, 2011).…”
Section: Functions and Distributionmentioning
confidence: 99%